Multi-frequency integrated profiles of pulsars - Johnston, S; Karastergiou, A; Mitra, D; Gupta, Y (2008)
We have observed a total of 67 pulsars at five frequencies ranging from 243 to 3100 MHz. Observations at the lower frequencies were made at the Giant Metre Wave Telescope in India and those at higher frequencies at the Parkes Telescope in Australia. We present profiles from 34 of the sample with the best signal to noise ratio and the least scattering. The general `rules' of pulsar profiles are seen in the data; profiles get narrower, the polarization fraction declines and outer components become more prominent as the frequency increases. Many counterexamples to these rules are also observed, and pulsars with complex profiles are especially prone to rule breaking. We hypothesise that the location of pulsar emission within the magnetosphere evolves with time as the the pulsar spins down. In highly energetic pulsars, the emission comes from a confined range of high altitudes, in the middle range of spin down energies the emission occurs over a wide range of altitudes whereas in pulsars with low spin-down energies it is confined to low down in the magnetosphere.